2015
DOI: 10.1192/pb.bp.114.047936
|View full text |Cite
|
Sign up to set email alerts
|

What is culturally informed psychiatry? Cultural understanding and withdrawal in the clinical encounter

Abstract: What is culturally informed psychiatry? What does it mean, and why is it important? These questions are discussed with a focus on the cultural aspects of the clinical encounter. The DSM-5 Outline for Cultural Formulation was developed as a method of assessing the cultural factors affecting the clinical encounter. It calls for the assessment of the cultural features of the relationship between the patient and the clinician; however, there is a lack of debate about what this means in practice. Clinicians run the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In fact, this ACSE dimension is the one that most pertains to the wider domain of empathic understanding, and not surprisingly it recalls the feelings of estrangement reported in some clinical vignettes [47] and in the studies about multilingual psychotherapeutic settings [57]. Further, it seems to be close to the notion of clinician’s uncertain attunement claimed by some scholars as a potential consequence of the ethnocultural diversity [39, 58, 68]. Hence, this result may contribute to the aforementioned debate about the clinician’s ability to sensitively feel the patient when the cultural diversity exacerbates the interpersonal otherness .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In fact, this ACSE dimension is the one that most pertains to the wider domain of empathic understanding, and not surprisingly it recalls the feelings of estrangement reported in some clinical vignettes [47] and in the studies about multilingual psychotherapeutic settings [57]. Further, it seems to be close to the notion of clinician’s uncertain attunement claimed by some scholars as a potential consequence of the ethnocultural diversity [39, 58, 68]. Hence, this result may contribute to the aforementioned debate about the clinician’s ability to sensitively feel the patient when the cultural diversity exacerbates the interpersonal otherness .…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, the issues related to the cross-cultural assessment in psychiatric settings have been widely considered, especially concerning the different psychopathological manifestations across cultures and the related diagnostic uncertainties [35][36][37]. Many authors have suggested the necessity of a culturally informed psychiatry [38,39], able to deal with the clinician's biases in detecting, understanding, and treating mental illness in foreign patients [40][41][42][43][44], and substantial efforts were made to improve both diagnostic sensitivity and therapeutic intervention, especially through the development of the Cultural Formulation Interview [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…The emic-etic perspective allowed us to discuss different kinds of knowledge and complementary data central to our investigation – for example, healthcare-seeking behaviours, understanding the sense of life from a Fang perspective following Simons D et al [ 41 ] through an objective, outsider perspective (etic) following Ruanoa. L. et al [ 42 ] and Leseth A.B [ 43 ], and from the participants’ point of view (emic). Data collection was conducted using two qualitative methods: semi-structured interviews and participant observation.…”
Section: Methodsmentioning
confidence: 99%
“…Elements of culture affect beliefs on health care, coping and help seeking, mental illness, and wellness and health services (SAMHSA, 2014a); therefore, implementing culture-informed care with an individual refugee in treatment must involve providers’ efforts to (a) learn about refugees’ native culture; (b) learn the meaning and expressions of the symptoms in the native culture; (c) learn how they translate to diagnosing and treating; and (d) establish an acceptable way of communication with each patient and resilience for recovery (Kortmann, 2010). The demand for culture-informed care is especially increasing in the two top tiers of the MHPSS for clinical treatment of mental disorders or illness for better treatment responses, compliance, and sustained recovery (Kirmayer, Groleau, Guzder, Blake, & Jarvis, 2003; Leseth, 2015). To increase positive outcomes and quality of psychosocial programs and mental health services, the two-pillar approach should be further promoted, while reinforcing the existing competencies in each setting.…”
Section: A Two-pillar Approach: Trauma-informed and Culture-informed ...mentioning
confidence: 99%